Family Care and the Fragile Persistence of At-Homeness in Genetic Kidney Disease - Yiying Wang (Health Medicine and Therapeutics, 2026)
This paper draws on participant observation and semi-structured interviews with the author’s grandmother and mother to examine how genetically inherited chronic kidney disease reshapes responsibility, care, and kinship within a Chinese family. Diagnosed with kidney failure at fifty and now managing thrice-weekly dialysis at eighty-three, the author’s grandmother lives alone despite her family’s wish that she move in, a choice she explains as necessary to preserve her remaining independence. Drawing on the phenomenological concept of at-homeness, the paper traces how illness reorganizes the personal, relational, material, and temporal dimensions of home, and how small daily acts, such as cooking her own breakfast and choosing her own clothes, allow the grandmother to resist the disease’s claim on her identity. The paper also identifies a paradox: caregiving intensive enough to guarantee safety can erode the very sense of self it aims to protect, a tension complicated by the family’s own admission that respecting the grandmother’s independence conveniently serves their interests as well. Because the underlying condition is heritable, the disease’s consequences extend beyond the grandmother’s own body: genetic testing revealed that the author and her mother carry the same mutation, prompting new family practices of secrecy, guilt, and planned disclosure to future partners. These findings suggest that family care under chronic genetic illness is negotiated not only through daily labor but through silence, timing, and responsibility toward kin not yet born.